Internal Сivilizational Content – Civilizational - W. Yiwei (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
From the point of the human civilization history the main purpose of “One Belt, One Road’ Project is to revise the provisions of west-oriented ideology according to which the continental civilizations are subordinate to the maritime ones and the East is subordinate to the West. At the same time, “One Belt, One Road’ Project helps to restore through the return of Eurasia as the center of world civilization and is aimed at the creation of a foundation for a new civilization based on the principles of “unity of man and heaven” and “unity of man and the sea”. From the point of Chinese civilization history, the above-mentioned Project contributes to its triune transformation: the transition from a continental type of civilization to the maritime one, from an agrarian civilization to an industrial one, from a regional civilization to a global one. «One Belt, One Road» Project shows the increased consciousness of Chinese civilization, reflects its self-confidence and is an expression of the theoretical, practical and philosophical aspects of Chinese wisdom, creating the “effect of three fives”: changes unseen over the five-thousand-year history by which a transformation of the traditional Chinese culture is meant; changes unseen over the last five hundred years by which the renewal of modern civilization is meant; changes unseen over the past fifty years by which a realization of the Chinese dream is meant. Together they lead to a simultaneous revival and transformation of an ancient civilization, and also allow us to talk about the conjugation of the Chinese and world dreams.